Keanekaragaman Makrozoobentos di Sungai Musi Desa Sungsang Kabupaten Banyuasin, Sumatera Selatan - Halimah Tussa’diyyah; Agus Purwoko; Mustafa Kamal (Jurnal Penelitian Sains, 2018)
Musi River Sungsang Village which is located near the settlement makes people throw garbage into the sea during high tides so that it will affect water quality and have an impact on macrozoobenthos. It is im-portant to know the diversity of macrozoobenthos in the waters of the Musi River in Sungsang Village, South Sumatra. This research was carried out from January 2018 to August 2018 in the Musi River in Sungsang Vil-lage, South Sumatra by using the method of direct observation and randomized group design. The research location was determined by purposive sampling method and divided into 4 stations, each station had 1 line transect and each line transect was taken as many as 10 samples. ANOVA, overley and correlation analysis are used to process data. Based on research conducted in the Musi River in Sungang Village, there were 14 ma-crozoobenthos taxa consisting of 3 classes: bivalves, gastropods and polychaeta. Index of macrozoobenthos di-versity in Musi River in Sungsang Village is classified as ranging from 0,000 – 1,733. Organic matter does not af-fect macrooobenthic in the Musi River in Sungsang Village, South Sumatra